Ideal harvest stage and quality descriptors of 5 banana cultivars based on 5 fruit diameters - Bolfarini, Ana Carolina Batista; Souza, Jackson Mirellys Azevêdo; Silva, Marcelo de Souza; Ferreira, Rafael Bibiano; Leonel, Magali; Tecchio, Marco Antonio; Leonel, Sarita (Emirates Journal of Food and Agriculture, 2020)
Quality attributes of fruits such as pH, titratable acidity, soluble solids, maturity indices, firmness, skin colour and sugar content should support choosing the choice of the most appropriate stage to harvest bananas. Therefore, this study aimed to identify the optimal harvest stage of different cultivars according to five fruit diameters. Through a randomized block design with 4 replicates, the following variables were evaluated such as pH, titratable acidity, soluble solids, maturity index, firmness, fruit peel colour and sugar content on the cultivars Prata-Anã, Maçã, FHIA 18, Grand Naine and Nanicão IAC 2001. Fruits from the second bunch of banana bundle were harvested when they reached the diameters of 32, 34, 36, 38 and 40 mm. Results showed that the harvest stages (i.e. banana fruit diameters) affect the fruit quality attributes among cultivars; thus, it is recommended to harvest the fruits of ‘FHIA 18’ with 34, 36 or 38 mm in diameters; Grand Naine with 38 or 40 mm; ‘Maçã’ and ‘Nanicão IAC 2001’ with 38 mm; and ‘Prata-anã’ with 34 or 36 mm.